The impact of human capital on the provision of agricultural products in the context of import substitution - Sycheva, Irina N.; Poltarykhin, Andrey L.; Dymchenko, Olga V.; Kurikov, Vladimir M.; Solopova, Natalia N.; Nepshekueva, Tamara S.; Karpova, Galina V. (Nexo Revista Científica, 2022)
Vegetable growing is an important sub-sector of agriculture. The provision of the region's population with vegetable products depends on its successful functioning. Vegetables contain vitamins, minerals, and fiber necessary for humans, which makes them an irreplaceable food product. The authors analyzed the current state of production and consumption of vegetable products in the region and made a forecast of the need for vegetable products until 2035, gave a number of recommendations to fully provide the population of the region with vegetable products. The transition of vegetable growing to a new level of technology development requires improvement, strengthening of human capital in the rural sector. Since in modern conditions the quality and quantity of products produced by the agro-industrial complex depends on the main characteristics of workers, therefore, special attention should be paid to changing the paradigm of agrarian education.